If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4(2x + 3) = x Reorder the terms: 5x + 4(3 + 2x) = x 5x + (3 * 4 + 2x * 4) = x 5x + (12 + 8x) = x Reorder the terms: 12 + 5x + 8x = x Combine like terms: 5x + 8x = 13x 12 + 13x = x Solving 12 + 13x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + 13x + -1x = x + -1x Combine like terms: 13x + -1x = 12x 12 + 12x = x + -1x Combine like terms: x + -1x = 0 12 + 12x = 0 Add '-12' to each side of the equation. 12 + -12 + 12x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = 0 + -12 12x = 0 + -12 Combine like terms: 0 + -12 = -12 12x = -12 Divide each side by '12'. x = -1 Simplifying x = -1
| -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 | | -6+7q=5q | | x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 | | -3/2=-2/5y-5/3 | | 1-2x+3=2x+8 | | -3/2=2/5y-5/3 | | ax-b=c(x-a) | | 6+14u=8 | | 13+3(3x+8)=x+3 | | -(x+3)+2=2x | | -8y-9=-10+9 | | 2/3u-8/9=-7/5 | | 6x=ln(10/9) | | 4x+-2y=18 | | 4k(-3mk)= |